Engagement to review financial statements as the instrument to ensure reliability of the information about the company - Lakis, Vaclovas; Miniotaitė, Justina (Information & Media, 2016)
Consumers of the corporate financial statements are expecting that information provided is reliable and accurate. Independent auditors review financial statements for some entities and give their opinion on its reliability. Audit as an obligatory instrument to review quality of financial statements is performed for the public interest companies and some other entities that meet certain criteria. For the rest of the entities audit is not obliged to perform. Mostly such entities are small and some of the medium-sized enterprises.Small and medium-sized enterprises represent meaningful part of Lithuania’s gross domestic product. Therefore, those enterprises have a significant impact on the country’s economics and the interests of the government institutions, other entities, and decisions of some individuals.Recently, the new auditors’ service that can be used by small and medium-sized enterprises, associations, apartment building and other building owners’ communities, gardeners’ communities, garage building and exploitation communities, charity and support funds, and other entities has been offered. This service was created to be used by the entities that would be satisfied by the given rational assurance on the financial statements reliability and financial audit, and would be a hard financial responsibility. It could be also used by the bigger corporations. This new auditors’ service is an engagement to review financial statements.Engagements to review financial statements had been introduced to ensure the financial statements’ reliability of the entities that are not obliged to perform annual audit. Engagements to review financial statements and audit have some similarities and differences. There are same phases for the performance of these two services. However, some of the actions and procedures in those phases are different. The differences are caused by the specifics of these services. When performing engagements to review financial statements, auditors do not perform some of the procedures that are mandatory to carry out when performing audit. Some of the other procedures volumes are smaller for engagement to review.Audit companies and their auditors are ready to adequately perform engagements to review financial statements for the entities.
Keywords: ...